Consumer Cosmopolitanism in the Age of Globalization - Prince, Melvin (Business Expert Press, 2012)
Cosmopolitans are individuals with a distinctive kind of extended national and international orientation, a global vision, and sense of belonging to the world. These people are sophisticated and importantly engaged in the cultures outside of local geographical boundaries. But what do we know about them as consumers—their origins, values, media usage, and buyer behavior? This unique book details much about this group, and fills a knowledge gap that has long been overlooked largely because other related marketing areas have overshadowed and overlooked the notion of cosmopolitan consumers. Until this book, in fact, there has been no single authoritative source that directly and comprehensively covers the field of consumer cosmopolitanism. This book also includes original essays by an all-star cast of contributors, giving you an introduction to a powerful new approach to marketing, eclectically packed with novel ideas and insights that noticeably advance the marketing field and bring it more fully into the age of globalization.
Keywords: Business & Economics / Consumer Behavior; Consumer behavior; dept.mkt; faculty_collection